If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2c + -3) + -7 = 2c + 5 Reorder the terms: 2(-3 + 2c) + -7 = 2c + 5 (-3 * 2 + 2c * 2) + -7 = 2c + 5 (-6 + 4c) + -7 = 2c + 5 Reorder the terms: -6 + -7 + 4c = 2c + 5 Combine like terms: -6 + -7 = -13 -13 + 4c = 2c + 5 Reorder the terms: -13 + 4c = 5 + 2c Solving -13 + 4c = 5 + 2c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2c' to each side of the equation. -13 + 4c + -2c = 5 + 2c + -2c Combine like terms: 4c + -2c = 2c -13 + 2c = 5 + 2c + -2c Combine like terms: 2c + -2c = 0 -13 + 2c = 5 + 0 -13 + 2c = 5 Add '13' to each side of the equation. -13 + 13 + 2c = 5 + 13 Combine like terms: -13 + 13 = 0 0 + 2c = 5 + 13 2c = 5 + 13 Combine like terms: 5 + 13 = 18 2c = 18 Divide each side by '2'. c = 9 Simplifying c = 9
| a/4=32 | | 9x+1.5=19.5 | | -5w+4w^2+9=0 | | 6a-4ifa=7 | | 30-15x+6x=32+16 | | 4x+31=-x+1 | | 4-11=3 | | (4x^2-32x-26)/(x-9) | | 2=-3d+14 | | 3+8x=-3(-1-7x) | | -15=c/9-10 | | k=25+10x | | (7-z)(3z-8)=0 | | 48x^2-x-15=0 | | 2(x+4)+6=50 | | -5(-3p+3)=8(6p-6) | | (3x-7)(4x+4)=0 | | 0.3=x(1+x) | | 88=2(6p+8) | | -2(y-6)+1=0 | | X(y+5)=66 | | -65=-8x-9 | | 2a^2+8ab=0 | | 2/9*9-4 | | lnx(x^4/4) | | 7a-4a-2a=5 | | 1441/2 | | 5x(x-3)= | | n(3n+2)=0 | | (5x+y)= | | 10p+9-11-p=-4p-8-6p | | 95=25+10*x |